2019
DOI: 10.1590/1413-785220192706207042
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Analysis of Acetabular Fractures Treated in a Quaternary Care Hospital From 2005 to 2016

Abstract: Objective:Analyze the clinical and sociodemographic data on acetabular fractures in a Brazilian quaternary care hospital and compare with data reported in the literature.Methods:A descriptive, analytical cross-sectional epidemiological study analyzing 87 patients with acetabular fractures at Hospital São Paulo (UNIFESP/EPM) between 2005 and 2016. Demographic variables such as age, sex, occupation, educational level and color were investigated. Acetabular fractures were classified according to the AO/OTA group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(14 reference statements)
2
3
0
1
Order By: Relevance
“…Our higher observed rates could be as a result of a relatively prolonged duration of surgery. Our findings were similar to the 12.6 % infection rate noticed by Cavalcante [8] . We did not however, record any cases of thromboembolic disease, same as in the study by Khan et al [9] , or early post-operative mortality compared to the 4.3% mortality identified by Jindal and collaborators [21] following acetabular fracture surgery.…”
Section: Other Early Complicationssupporting
confidence: 92%
See 2 more Smart Citations
“…Our higher observed rates could be as a result of a relatively prolonged duration of surgery. Our findings were similar to the 12.6 % infection rate noticed by Cavalcante [8] . We did not however, record any cases of thromboembolic disease, same as in the study by Khan et al [9] , or early post-operative mortality compared to the 4.3% mortality identified by Jindal and collaborators [21] following acetabular fracture surgery.…”
Section: Other Early Complicationssupporting
confidence: 92%
“…About 26% (15/57) of patients developed immediate or early post-operative complications. This was similar to the 22 % complication rate noticed by Cavalcante and colleagues [8] . The most significant early post-operative complications following the K-L approach are shown on table III.…”
Section: Immediate and Early Post-operative Complicationssupporting
confidence: 91%
See 1 more Smart Citation
“…2,20 In younger patients, posterior wall fracture was the most common fracture pattern seen, followed by transverse with posterior wall, and T-type fractures. 21,22 Ferguson et al 1 found that anterior column fracture, and anterior column with posterior hemitransverse fracture were more common among the geriatric patients as compared to the younger patients, and transverse with posterior wall fracture pattern was more common among the younger patients.…”
Section: Fracture Characteristicsmentioning
confidence: 99%
“…Male to female ratio was 3.4:1 with male preponderance. Marcelo C C et al, 8 in 87 patients analysed 75 (77.3%) male and 10 females cases with fracture acetabulum. Boudissa M et al, 9 assessed 156 cases and had a majority of 126 (81%) male patients.…”
Section: Discussionmentioning
confidence: 98%